The use of index images for decoding the vegetation cover of inner mountain Dagestan, Russia - R. T. Radzhabova; N. A. Alekseenko; B. M. Kuramagomedov; Z. Sh. Tazhudinova; Z. M. Sultanov (Юг России: экология, развитие, 2021)
Aim. Selection and analysis of index images suitable for deciphering the vegetation cover in the conditions of inner mountain Dagestan.Methods. The study was carried out on the basis of multi-temporal satellite images of high spatial resolution, obtained by the imaging system of the Sentinel-2 series satellite, using methods of digital processing of geoimages. Processing was carried out using the capabilities of the Google Earth Engine geoservice.Results. Multi-temporal index images were obtained for the territory of inner mountain Dagestan. The time series of seasonal changes in the indices (NDVI, SAVI, EVI) were analyzed, making it possible to reveal the phenological patterns of vegetation and to map the vegetation cover on this basis. Schemes for decoding vegetation have been created by which areas are distinguished according to the following characteristics: devoid of vegetation, herbaceous vegetation of varying degrees of density or woody (deciduous and coniferous).Conclusion. When studying vegetation cover using index images in a range of natural conditions, it is necessary to take into account the natural features of the territory, as well using additional sources of spatial information including field research methods.